PENGEMBANGAN MEDIA PEMBELAJARAN SMART APPS CREATOR PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) SISWA KELAS IX UPT SMP NEGERI 2 KELARA KABUPATEN JENEPONTO - Jannah, Miftahul (Almeera Education, 2025)
Abstract. Development of Smart Apps Creator Learning Media in Science Subjects for Class IX Students of UPT SMP Negeri 2 Kelara, Jeneponto Regency. This study aims to develop an Android-based Smart Apps Creator learning media. The development model used in this study is the ADDIE Model. The result of this research is a product in the form of learning media Smart Apps Creator. The results of the media validation analysis obtained 4 with a valid assessment category, the results of material validation obtained 3.9 with a valid assessment category, and the results of student responses obtained an average value of 106.6 with a very interesting assessment category. The average score of the teacher's response assessment is 4.2 with a good category. The overall responses of students, validators, and teachers in developing the Smart Apps Creator Learning media in the Science Subjects of Class IX students of UPT SMP Negeri 2 Kelara, Jeneponto Regency were declared feasible and well used in the teaching and learning process. Keywords: Development, Learning Media Smart Apps Creator, model ADDIE development. IPA